Enhanced multifaceted model for plasmon-driven Schottky solar cells with integrated thermal effects - Brahim Aïssa; Ahmer A. Baloch; Adnan Ali; Anirban Mitra (Scientific Reports, 2025)
Abstract This paper explores the development of an opto-thermal-electrical model for plasmonic Schottky solar cells (PSSCs) using a comprehensive multiphysics approach. We simulated the optical properties, power conversion efficiencies, and energy yield of PSSCs with varying nanoparticle (NP) configurations and sizes. Our spectral analysis focused on the absorption characteristics of these solar cells, examining systems sized 3 × 3, 5 × 5, and 7  × 7, with NP radii ranging from 10 to 150 nm. The study addresses a significant gap in solar cell research by presenting a novel multi-physics energy yield model for PSSCs decorated with gold nanoparticles (Au-NPs) on silicon absorbers. This integrated framework uniquely couples optical, electrical, and thermal responses for the prediction of global energy yield maps. Total spectral heat absorption was evaluated over a range of 300 nm to 1200 nm. This spectral heating was further deconvoluted into nanoparticle heating and thermalization heating in a silicon absorber. The findings indicated that the 5 × 5 NP array with a 70 nm radius enhances electrical performance, with the short-circuit current density (Jsc) reaching 11.54 mA/cm2—A 47% improvement compared to traditional bare silicon Schottky cells of 2 μm thickness. However, this electrical enhancement was also accompanied by a significant increase in heat generation within the nanoparticles, with thermal gains up to 182.5% relative to the bare silicon cells. This substantial rise in thermal energy highlights the critical need for advanced thermal management strategies to mitigate overheating and ensure the overall efficiency of plasmonic-enhanced solar cells. Enhanced energy yield maps confirm the model’s predictions, showing improved outputs globally, especially in sunny regions with potential annual energy yield gains up to 80 kWh/m2.